Does indulgence in watching live streams really reduce perceived stress? A cross-lagged panel study - Wei Wang; Jingyu Zhao; Siqi Feng; Chenrui Xu; Chongdi Zhong; Hongzhi Sun (Computers in Human Behavior Reports)
People are investing more time in live streaming, and stress relief is one of their main motivations. The purpose of this study is to explore the causal relationship between viewers' live streaming dependence and perceived stress. We surveyed college students using the Live Streaming Dependency Scale and the Chinese Perceived Stress Scale, and constructed a cross-lagged panel model with questionnaire data. The results showed that live streaming dependence could not alleviate viewers' perceived stress, but rather became a facilitator. As time progresses, perceived stress reduces viewers' live streaming dependence. The results of this study suggest that indulgence in live streaming is not an antidote to stress relief. Practical and effective professional support should be sought when experiencing stressful events.